2010
DOI: 10.1128/jvi.01855-09
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Cell Lines with Experimental and Natural Ovine Scrapie Agents

Abstract: Mouse bioassay remains the gold standard for determining proof of infectivity, strain type, and infectious titer estimation in prion disease research. The development of an approach using ex vivo cell-based assays remains an attractive alternative, both in order to reduce the use of mice and to hasten results. The main limitation of a cell-based approach is the scarcity of cell lines permissive to infection with natural transmissible spongiform encephalopathy strains. This study combines two advances in this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Cell lines that have been successfully infected include microglial cells as well as epithelial cells, fibroblasts and myoblasts, which have all been demonstrated to persistently replicate an array of prion strains in vitro [98,99,100,101,102,103,104,105,106,107,108]. Curiously, a rabbit kidney epithelial cell line genetically engineered to express PrP C of different species was shown to be susceptible to a variety of prion strains isolated from different sources [99,100,101,102,103,104,105,109]. Several primary cell culture models for prion replication have been reported, some of which show cytopathic effects upon infection [110,111,112,113,114,115].…”
Section: Cellular Models For Studying Prpsc Formationmentioning
confidence: 99%
“…Cell lines that have been successfully infected include microglial cells as well as epithelial cells, fibroblasts and myoblasts, which have all been demonstrated to persistently replicate an array of prion strains in vitro [98,99,100,101,102,103,104,105,106,107,108]. Curiously, a rabbit kidney epithelial cell line genetically engineered to express PrP C of different species was shown to be susceptible to a variety of prion strains isolated from different sources [99,100,101,102,103,104,105,109]. Several primary cell culture models for prion replication have been reported, some of which show cytopathic effects upon infection [110,111,112,113,114,115].…”
Section: Cellular Models For Studying Prpsc Formationmentioning
confidence: 99%
“…Autopsies of Parkinson disease patients revealed that Lewy bodies had formed on healthy are needed. These may include the use of transgenic mice, cell lines which are permissive to infection 12 and experimental animals such as sheep, calves, goats, minks, ferrets and non-human primates (reviewed in ref. 9).…”
Section: Alimentary Prion Infectionsmentioning
confidence: 99%
“…An alternate hypothesis is to suggest that in prion infection with low or poor replicative ability ( i.e ., due to the factors mentioned above) the balance is switched in favor of degradation of agent, thereby preventing or dramatically slowing pathogenesis. This may occur both within any given cell (and not exclusively to degradative or phagocytic cell types), in fact it is well known that there are limited in vitro cell infection models in the prion field due to the relevant inability to infect numerous cell types with a variety of prion strains even within the same species [76], and within the complexity of the host innate immune response.…”
Section: Resultsmentioning
confidence: 99%